Qualitative Study of Accountability Strategies of Public Universities from the Viewpoint of Higher Education Experts Accountability Strategies of Public Universities - Abbas Abbaspour; Mohsen Shakeri; Hamid Rahimian; Maghsood Farasatkhah (Allameh Tabataba'i University Press, 2015)
The Purpose of this study was to discover the accountability strategies of public universities.Qualitative data achieved by semi-structured interviews with 20 higher education experts and faculty members. In the procedural analysis of the findings, using analytical techniques of Strauss and Corbin. Participants of the present research were selected based on repetition logic and were selected in line with the theory which is known as theoretical sampling and it lasted till the collected data reached the point of saturation. Data which were carried out by using Strauss & Corbin analytical techniques reveals 6 categories that explain strategies of public universities accountability. This strategies / categories include: 1.University autonomy (non-interference of government, giving authority to universities, university autonomy, scientific freedom), 2.Participation (students and professors in universities, university members in society, outside stakeholders in university-related issues), 3.Scientific-applied interactions (with other educational institutes or other sections), 4.Internationalization of universities, 5.Applicability, 6.Supply and allocation of financial resources.